(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The current analysis was performed by 100 high school science science students to establish the association between the research practices family atmosphere of science students studying at Haryana High School. The findings of the analysis found that there is a strongly positive association between the rejection elements of the family setting and the study habits of boys, which indicates that the study habits of boys will be influenced. Moreover, the association of certain components of the family setting with study behaviors among boys is substantially negative. The research also showed that there was no substantial gap in the home setting between boys girls enrolled in higher secondary school education. The research also has consequences for educators parents.